PENGEMBANGAN DONGENG BERBASIS AUGMENTED REALITY SEBAGAI BAHAN LITERASI DALAM MASA PANDEMI - Wulan Tri Puji Utami; Novy Trisnani (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2021)
Strengthening literacy in the midst of the Covid-19 pandemic was a challenge for academics and educational practitioners to continue in encouraging literacy. Literacy was one of the important programs in education because literacy culture in Indonesia was still low. The pandemic had hampered the implementation of the School Literacy Movement. Therefore, this research aimed to: 1) develop reading materials in the form of Augmented Reality-based fairy tales for elementary school students so that they became supporting tools of the School Literacy Movement during the pandemic; 2) evaluate the effectiveness of Augmented Reality-based fairy tales in fostering literacy habits in elementary school students. This research was a development research in elementary school students which refered to the ADDIE development stage which had been modified to suit the research objectives. The development stages were: 1) Analysis; 2) Design; 3) Development; 4) Implementation; and 5) Evaluation. The research data were collected through observation, documentation, questionnaires, and tests. The data analysis techniques in this research were divided into four, namely preliminary studies, product development processes, product feasibility tests, and product practicality tests. The research results showed that stories based on AR developed as literacy material for students in Elementary Schools was considered worthy of a good category after validation tests were carried out by material experts, media experts, and practitioners. Keywords: augmented reality, digital literacy. References:   Apriyani,  M.E., Huda, M., &  Prasetyaningsih, S.  2016. Analisis Penggunaan Marker Tracking Pada Augmented Reality Huruf Hijaiyah. JURNAL INFOTEL - InformatikaTelekomunikasiElektronika,8(1),https://doi.org/10.20895/infotel.v8i1.54. Arini, A., & Fitrana, E.A. 2019. Pengembangan Aplikasi Katalog Rumah Berbasis Augmented Reality Menggunakan Algoritma FAST. JISKA (Jurnal Informatika Sunan Kalijaga), 4(1), 9. http://orcid.org/0000-0002-9805-2866. Asfandiyar, A.Y. 2010. Cara Pintar Mendongeng. Bandung: Mizan. Habsari, Z. 2017. Dongeng sebagai Pembentuk Karakter Anak. Bibliotika: Jurnal Kajian Perpustakaan dan Informasi.Vol 1 No. 1-April 2017(21-29). http://dx.doi.org/10.17977/um008v1i12017p021. Khansa, A.R. 2017. The Pengembangan Aplikasi “Indonesian Landmark” Berbasis Android dengan Teknologi Augmented Reality. KOPERTIP : Jurnal Ilmiah ManajemenInformatikaDanKomputer,1(2),77–84. https://doi.org/10.32485/kopertip.v1i02.12 Krissandi, A.D.S. 2018. Buku Cerita Anak Yang Bermuatan Pendidikan Anti Korupsi. NATURALISTIC : Jurnal Kajian Penelitian   Pendidikan  Dan  Pembelajaran,2(2), 139. https://doi.org/10.35568/naturalistic.v2i2.120 Mutiasih, P., Iswara, P., Nugraha, & Trisna. 2021. Pengembangan Buku Bercerita bergambar berbasis Pendidikan karakter Dalam menumbuhkan Budaya Literasi Siswa Kelas II Sekolah Dasar. Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 5(1), 560. https://doi.org/10.30738/tc.v5i1.9470 Nurgiyantoro, B. 2013. Sastra Anak: Pengantar Pemahaman Dunia Anak. Yogyakarta: Gadjah Mada University Press. OECD.  2019.  Programme  for  International  Students  Assessment  (PISA)  Result  from  PISA 2018. Indonesia-Country Note-PISA 2018 Result, Volumes I-III. Puspasari,  R., & Suryaningsih,  T.  2019.  Pengembangan  Buku  ajar  kompilasi  Teori Graf dengan Model ADDIE. Journal of Madives Vol. 3(1), 137-152. https://doi.org/10.31331/medivesveteran.v3i1.702 Scrivner, O., Madewell, J., Buckley, C., & Perez, N. 2017. Augmented reality digital technologies (ARDT) for foreign language teaching and learning. FTC 2016 - Proceedings of Future Technologies Conference, 395–398. https://doi.org/10.1109/FTC.2016.7821639 Sugiyono. 2015. Metodologi Penelitian Pendidikan. Bandung: Alfabeta Sumartini, L.P.A., Antara, P.A.,   &   Magta, M.  2017.   Pengaruh   Metode Dongeng Interaktif  Terhadap  Karakter  Anak  Pada  Taman  Kanak-Kanak  Kuncup  Harapan  Singaraja. Jurnal Pendidikan Anak Usia Dini. Vol. 5, No. 1. Yuen, S., et al. 2011. Augmented Reality: An Overview and Five Directions for AR in Education. Journal of Education Technology Development and Exchange, 4(1), 119-140. Doi: 10.18785/jetde.0401.10. Wangid, M. N., Mustadi, A., & Putri, A. R. 2018. Fairy Story Integration For Meaningful Classroom. Cakrawala Pendidikan, 37(2), 6–8.